Investigating the cognitive precursors of emotional response to cancer stress: Re‐testing Lazarus's transactional model. (24th September 2012) - Hulbert‐Williams, N. J.; Morrison, V.; Wilkinson, C.; Neal, R. D.
Abstract : Objectives. Lazarus's Transactional Model of stress and coping underwent significant theoretical development through the 1990s to better incorporate emotional reactions to stress with their appraisal components. Few studies have robustly explored the full model. This study aimed to do so within the context of a major life event: cancer diagnosis. Design. A repeated measures design was used whereby data were collected using self‐report questionnaire at baseline (soon after diagnosis), and 3‐ and 6‐month follow‐up. Methods. A total of 160 recently diagnosed cancer patients were recruited (mean time since diagnosis = 46 days). Their mean age was 64.2 years. Data on appraisals, core‐relational themes, and emotions were collected. Data were analysed using both Spearman's correlation tests and multivariate regression modelling. Results: Longitudinal analysis demonstrated weak correlation between change scores of theoretically associated components and some emotions correlated more strongly with cognitions contradicting theoretical expectations. Cross‐sectional multivariate testing of the ability of cognitions to explain variance in emotion was largely theory inconsistent. Conclusions. Although data support the generic structure of the Transactional Model, they question the model specifics. Larger scale research is needed encompassing a wider range of emotions and using more complex statistical testing. Statement of Contribution: What is already known on this subject?:   Stress processes are transactional and coping outcome is informed by both cognitive appraisal of the stressor and the individual's emotional response (Lazarus & Folkman, 1984 ).   Lazarus (1999) made specific hypotheses about which particular stress appraisals would determine which emotional response, but only a small number of these relationships have been robustly investigated.   Previous empirical testing of this theory has been limited by design and statistical limitations. What does this study add?:   This study empirically investigates the cognitive precedents of a much larger range of emotional outcomes than has previously been attempted in the literature.   Support for the model at a general level is established: this study demonstrates that both primary and secondary appraisals, and core‐relational themes are important variables in explaining variance in emotional outcome.   The specific hypotheses proposed byLazarus (1999) are not, however, supported: using data‐driven approaches we demonstrate that equally high levels of variance can be explained using entirely different cognitive appraisals than those hypothesized.